Digitalisasi Administrasi Desa Kuta Mbelin Berbasis SID Untuk Tata Kelola Pemerintahan Yang Efektif Berkelanjutan - Seniman; Syahril Efendi; Fauzan Nurahmadi; Fuzy Yustika Manik; T. Henny Febriana Harumy; Ivan Jaya; Yeni Absah; Muhammad Romi Syahputra; Liana Dwi Sri Hastuti; Pauzi Ibrahim Nainggolan; Tulus Joseph Herianto; Dewi Sartika Br Ginting; Yudhistira (STMIK Royal, 2026)
Abstract: The digital transformation of village administration has become an urgent need to enhance public service efficiency and ensure transparent local governance. This study analyzes the implementation of the Village Information System (SID) in Kuta Mbelin Village, STM Hulu Subdistrict, Deli Serdang Regency, as a mechanism for supporting administrative digitalization. It also evaluates the role of information technology in village governance and the integration of village statistical data within the framework of the Sustainable Development Goals (SDGs). The research employs a combination of literature review, field observation, and interviews with village officials and community members. The findings indicate that the adoption of SID in Kuta Mbelin Village improves administrative efficiency, accelerates public service delivery, and enables evidence-based data management that supports sustainable village development planning. This study recommends enhancing SID by integrating data analytics and strengthening information security to maximize its usefulness in village governance. Keywords: village digitalization; village information system; governance; SDGs; kuta mbelin village Abstrak : Transformasi digital dalam administrasi desa menjadi kebutuhan mendesak guna meningkatkan efisiensi layanan publik dan tata kelola pemerintahan yang transparan. Penelitian ini menganalisis implementasi Sistem Informasi Desa (SID) di Desa Kuta Mbelin, Kecamatan STM Hulu, Kabupaten Deli Serdang, dalam mendukung digitalisasi administrasi desa. Studi ini juga mengevaluasi peran teknologi informasi dalam tata kelola pemerintahan desa serta integrasi data statistik desa dalam perspektif Sustainable Development Goals (SDGs). Metode penelitian yang digunakan meliputi studi literatur, observasi lapangan, dan wawancara dengan perangkat desa serta masyarakat. Hasil penelitian menunjukkan bahwa penerapan SID di Desa Kuta Mbelin meningkatkan efisiensi administrasi, mempercepat pelayanan publik, dan memungkinkan pengelolaan data berbasis bukti yang mendukung perencanaan pembangunan desa berkelanjutan. Studi ini merekomendasikan optimalisasi SID dengan integrasi analitik data dan keamanan informasi untuk meningkatkan daya guna dalam tata kelola desa. Kata Kunci: digitalisasi desa; sistem informasi desa; tata kelola pemerintahan; SDGs; desa kuta mbelin